2021
DOI: 10.2147/opth.s308585
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Central Corneal Thickness and Ganglionic-Inner Plexiform Cell Layer and Retinal Nerve Fibre Layer Thickness in Normal Subjects

Abstract: Purpose To determine the relationship between central corneal thickness (CCT), ganglionic cell-inner plexiform layer thickness and macular nerve fibre layer (RNFL) thickness as measured by optical coherence tomography in a cohort of healthy subjects. Methods Sixty healthy eyes from 60 subjects were included in this study. All subjects had a standard slit-lamp examination and optical coherence tomography. Central corneal thickness was measured using the Optopol spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
1
0
1
Order By: Relevance
“…Few studies have examined the association between CCT and RNFL thickness in healthy individuals and reported different results. The results of studies performed on healthy individuals mainly indicate no significant association between CCT and RNFL thickness or an inverse association between these 2 parameters 59–61. Given the low regression coefficient in the final model in the present study, the association between CCT and RNFL thickness in children does not seem to be clinically significant.…”
Section: Discussioncontrasting
confidence: 66%
“…Few studies have examined the association between CCT and RNFL thickness in healthy individuals and reported different results. The results of studies performed on healthy individuals mainly indicate no significant association between CCT and RNFL thickness or an inverse association between these 2 parameters 59–61. Given the low regression coefficient in the final model in the present study, the association between CCT and RNFL thickness in children does not seem to be clinically significant.…”
Section: Discussioncontrasting
confidence: 66%
“…That is not surprising considering their anatomical and physiological independence as they explain this finding in their study. 8 The current result showed that there was significant negative correlation between corrected IOP and total RNFL in the studied POAG patients (r= -0.547, p<0.001). There was significant negative association between corrected IOP and superior RNFL in the studied POAG patients (r= -0.559, p<0.001), and there was significant negative association between corrected IOP and inferior RNFL in the studied POAG patients (r= -0.501, p<0.001).…”
Section: Ophthalmologysupporting
confidence: 52%